2002
DOI: 10.1002/qua.10307
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical justification of empirical additivity schemes for conformational energies

Abstract: Additivity of conformational energy of saturated molecules has been studied using the perturbation theory for density matrix. Analytical expressions for both total and conformational energies have been obtained and analyzed up to the third-order members. It is shown that the conformational energy of compounds under investigation can be presented as a sum of transferable increments corresponding to the energies of separate conformational segments and their sequences. The role of end groups in determination of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…This leads to the second problem: How much does each gauche conformation contribute to the total energy of a conformer? Several theoretical investigations focused on this question [2,[21][22][23] and found that the energy is essentially additive provided that the gauche conformations are sufficiently separated by trans segments. Cumulated gauche sequences deviate from additivity as local interactions can have either a stabilizing or destabilizing effect.…”
Section: N-alkane Conformationsmentioning
confidence: 99%
“…This leads to the second problem: How much does each gauche conformation contribute to the total energy of a conformer? Several theoretical investigations focused on this question [2,[21][22][23] and found that the energy is essentially additive provided that the gauche conformations are sufficiently separated by trans segments. Cumulated gauche sequences deviate from additivity as local interactions can have either a stabilizing or destabilizing effect.…”
Section: N-alkane Conformationsmentioning
confidence: 99%
“…Für Decan hingegen führt jede Faltung durchschnittlich zu einer Strafe von 2,5 kJ mol −1 , was gut zur allgemein bei Alkanen assoziierten Faltungsstrafe von 2 kJ mol −1 passt. [4,98] Die Stabilität der gefalteten Ester könnte dadurch erklärt werden, dass die gauche-Faltung die Bildung von stabilisierenden, intramolekularen H-Brücken zwischen dem Carbonyl-O und den H in γ-Position begünstigt.…”
Section: Eigenschaften Der Estergruppeunclassified